2021
DOI: 10.1128/jvi.02136-20
|View full text |Cite
|
Sign up to set email alerts
|

The Avian Retroviral Receptor Tva Mediates the Uptake of Transcobalamin Bound Vitamin B 12 (Cobalamin)

Abstract: The Avian sarcoma and leukosis viruses (ASLVs) are important chicken pathogens. Some of the virus subgroups, including ASLV-A and K, utilize the Tva receptor for cell entrance. Though Tva was identified three decades ago, its physiological function remains unknown. Previously, we have noted an intriguing resemblance and orthology between the chicken gene coding for Tva and the human gene coding for CD320, a receptor involved in cellular uptake of transcobalamin (TC) in complex with vitamin B12/cobalamin (Cbl).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
(83 reference statements)
1
6
0
Order By: Relevance
“…The absence of distinct phenotype is consistent with the mouse model, where CD320 knock-out does not completely abrogate the cbl import, and clinically asymptomatic human cases with CD320 defect [49,50], implying a parallel transport mechanism [23,24]. An alternative cbl uptake pathway is also visible in the tva chicken cells, where the uptake of cbl-transcobalamin remains significantly above the background level [21]. MMA is the most sensitive marker of altered cbl metabolism, whereas other metabolites will be analyzed in the inbred Tva KO line.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The absence of distinct phenotype is consistent with the mouse model, where CD320 knock-out does not completely abrogate the cbl import, and clinically asymptomatic human cases with CD320 defect [49,50], implying a parallel transport mechanism [23,24]. An alternative cbl uptake pathway is also visible in the tva chicken cells, where the uptake of cbl-transcobalamin remains significantly above the background level [21]. MMA is the most sensitive marker of altered cbl metabolism, whereas other metabolites will be analyzed in the inbred Tva KO line.…”
Section: Discussionsupporting
confidence: 71%
“…In addition to its function as ALV receptor, Tva was recently identified as a specific receptor for cbl-saturated transcobalamin necessary for efficient cbl internalization into cells [21]. Thus, Tva ensures the bioavailability of cbl for internal conversions of MMA-CoA to succinyl-CoA and remethylation of homocysteine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 E ). Studies have indicated that Tva is related to the uptake of transcobalamin-bound vitamin B 12 /Cbl ( 29 ). The ability to internalize vitamin B 12 /Cbl of DF-1-rTva was detected using the confocal assay.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, precise editing of key sites of cell receptors can not only resist virus infection but will also not affect the physiological function of the receptor protein, which will be an important direction of antiviral research in the future. Tva is involved in TC-mediated Cbl uptake ( 29 ). Although Tva-deficient gene-edited chickens have been generated and could completely resist ALV-K infection, they exhibit specific Cbl metabolic disturbances due to the lack of Tva ( 42 ).…”
Section: Discussionmentioning
confidence: 99%